Effect of Jinten Hitam Seeds Oil (Nigella sativa L.) In adenocarsinoma Mammae C3H Mice In Vivo An Experimental Study on C3H Mice Inoculated With Cancerous Tissue - Suprijono, Agus; Sumarno, Sumarno; Hanugalih, Hanugalih (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2011)
Background: Jinten hitam (Nigella sativa L.) oil is a liquid made from Jintem hitam seeds which has been known to contain Thymoquinone having anti-cancer efect. Many cancer patients turn to cheaper alternative therapy including the traditional therapy. The objective of this experimental was to evaluate anti-cancer effect of Jinten hitam seeds oil in adenocarsinoma mammae C3H mice.Design and Methods: In this xperimental research with pre post test randomized control group design for 21 days, 24 C3H mice with tumor were divided into 4 group. K-I serves as a control given standard diet and aquades, K-II given standard diet, aquades and first dose of Jinten Hitam oil (0.1 ml/days), K-III given standard diet, aquades and second dose of Jinten Hitam oil ( 0.2 ml/days) and K-IV given standard diet, aquades and third dose of Jinten Hitam oil ( 0.3 ml/days). The volume was recorded at the day 21.Results: mean of the effect of Jinten hitam oil effect in adenocarcinoma mammae for the four group were 158.83 mm³, 259.73 mm³, 191.13 mm³, K-IV 126.27 mm³ respectively. Pair t-test and Wilcoxon test showed significant difference between First dose pre-First dose post and Second dose pre-second dose-post (p<0.05) and Anova test showed no significant difference between K-I K-II, K-I K-III, K-I K-IV, K-II K-III, K-II K-IV, K-III K-IV (p>0.05).Conclusion: Jinten Hitam oil has effect on the volume of Adenocarcinoma mammae in C3H mice (Sains Medika, 3(2):129-134).